PENGARUH KOMPETENSI WIRAUSAHA TERHADAP STRATEGI, KINERJA BISNIS DAN DAYA SAING USAHA KECIL DI SULAWESI SELATAN - Sultan Sultan (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
This study aims to determine the influence of entrepreneurial competence to strategy and business performance and determine the effect of the power of small business performance saing.Permasalahan in this study is how the influence of entrepreneurial competence, external factors on the competitiveness of small businesses in South Sulawesi. At this study entrepreneurial competence variables and external factors were placed as exogenous variable, being variable business strategy, business performance and competitiveness of small businesses processing as endogenous variable. This study uses a pattern of explanation (explanatory research), the method of analysis is structural equation modeling (SEM). This research was conducted in the province of South Sulawesi with mengam-bil in the study sample of 100 small business with seven (7) districts and 1 (one) cities of Gowa, Takalar, District Je'ne Ponto, Kabuapten Bulukumba, Pangkep, Barru, Sidrap and Makassar. In this peneitian found that the competence of entrepreneurs have a positive and significant impact on the business strategy and the competitiveness of small businesses in South Sulawesi. Other findings that increase the competitiveness of Small Business is through the main means of entrepreneurial competence through business strategies and business performance.